Evaluation of the Effect of Earth Dam Construction on Gully Erosion Control from the Perspective of Watershed Residents in Mazayjan Watershed of Fars Province - Seyed Masoud Soleimanpour; Majid Soufi; Hojatolah Keshavarzi (پژوهش‌های آبخیزداری, 2022)
Most watershed management projects are designed and implemented with the aim of controlling soil erosion and floods, reducing their destructive consequences. Therefore, evaluating their impact is one of the most essential and important prerequisites for success. The present study evaluated the of the effect of earth dam construction on gully erosion control from the perspective of watershed residents in Mazayjan Zarrinudasht watershed located in the south of Fars Province. A questionnaire consisting of 32 questions from a range of 5 Likert options was prepared, and filled with a face-to-face interview with 200 watershed residents. Responses were analyzed in terms of demographic characteristics (gender and occupation) by SPSS software (version 16). Findings showed that 38.3% of women, 32.7% of men, and 47.3% of farmers with land believed that the construction of earth dam has improved the region and the living conditions. 59.6% of women, 60.8% of men and 69.1% of farmers with land had a positive evaluation of the effect of earth dam construction on gully erosion control. 59.5% of women, 60.1% of men and 69.1% of farmers with land had the highest percentages of agreeing to similar activities in the region. It is suggested that considering the positive view and tangible experience of the watershed residents of this region in the effectiveness of the construction of the earth dam, serious efforts be made to promote, plan, implement, operate and maintain watershed management projects.